PROPOSED PRODUCT REQUIREMENT TO INCREASE ADOPTION RATE OF DIGITAL SME PLATFORM AT BANK SBNG - Sonyah, Dina
Digital technology has rapidly grown in Indonesia both for consumer or business needs. BANK SBNG as one of the Banks that plays in SME segments introduces their new digital product namely Digital SME Platform as their strategy to face their business challenges while capturing opportunities of digital growth. However, despite the rapid growth of technology, the participation and adoption rate of SMEs in digital is still low. It leads to the problem faced by Bank SBNG about the adoptions of Digital SME Platform. This research is conducted to give proposed product requirement to increase adoption rate of Digital SME Platform. Qualitative research methodology is used to gain information and identify alternative solutions. The primary data gathered is from interviewing 25 existing SME customers as their targeted users. For analysis technique, descriptive analysis is performed. The result of this research shows there are 21 factors that considered important, those factors are: (1)Digital Ecosystem Capability; (2)Features Capability: (3)Features Flexibility; (4)User Interface/ User Experience (UI/UX); (5)Fees; (6)Loyalty Program; (7)Data Consent; (8)Data Period; (9)Security; (10)Help Centre; (11)Transaction Limit; (12)Legal and Trustworthiness; (13)Language; (14)Information Availability; (15)Platform Accessibility; (16)Transaction Authorization; (17)User Access Management; (18)Pricing; (19)Speed; (20)Community Coverage; (21)Community Quality.